Double Haploid Development and Assessment of Androgenic Competence of Balkan Pepper Core Collection in Bulgaria - Stanislava Grozeva (MDPI AG, 2021)
This study was designed to assess the androgenic potential of 180 pepper accessions and 11 progenies (four F1 and seven BC) possessing PMMoV resistance in order to complement an ongoing pepper breeding program. The experiment was carried out in 10 replications with 20 anthers for each accession in two different induction mediums from 2017 to 2019. The highest androgenic response was observed in culture medium 17-2 but differences between two mediums were nonsignificant. From a total of 191 genotypes, 102 genotypes expressed a potential for direct embryogenesis. Embryo induction was seen to be genotype-dependent and decreased in the following order: Pumpkin > Conical > Bell or blocky > Round > Elongate as the most responsive genotypes with over 10% reacted anthers being observed in CAPS-23, CAPS-29, CAPS-127, CAPS-157, CAPS-169, F1 and BC 887 derived from CAPS-23. The number of regenerated plants was higher in the conical group and least in the round varietal group. Regenerated plants were examined visually and by flow cytometry for identification of spontaneous doubled haploids (DH) and haploids. Those originating from F1 and BC progenies were additionally evaluated by a CAPS marker targeting L4 allele for resistance against PMMoV. Obtained results revealed two groups consisting of homozygous susceptible and resistant plants. Therefore, use of anther culture in ongoing breeding will greatly facilitate the pepper genetic improvement.